2010
DOI: 10.1021/jp106593d
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Calculations on Site-Dependent Dissolution Potentials of Supported and Unsupported Pt Particles

Abstract: Site-dependent redox potentials of the Pt dissolution reaction, Pt → Pt2+(aq) + 2e−, from Pt particles with and without carbon supports were calculated by a first principles method. The calculation result showed a clear site-dependence in which the redox potentials for the Pt atoms at edges are lower than those for Pt atoms at flat surfaces. This site-dependence is roughly correlated with the d-band center of the dissolving Pt atom, and Pt atoms with higher d-band centers dissolve more easily to the solution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 52 publications
(98 reference statements)
6
119
0
Order By: Relevance
“…DFT models describing the dissolution of metal surfaces yielded similar results. [ 49,50 ] According to our present understanding, the coordinatively unsaturated (CUS) sites marked in Figure 2 a, which are located on the terraces, are the active sites for oxygen evolution on MnO 2 . [ 47 ] DFT calculations suggest this to be the case for RuO 2 and other rutile oxides.…”
Section: Theoretical Calculationsmentioning
confidence: 64%
“…DFT models describing the dissolution of metal surfaces yielded similar results. [ 49,50 ] According to our present understanding, the coordinatively unsaturated (CUS) sites marked in Figure 2 a, which are located on the terraces, are the active sites for oxygen evolution on MnO 2 . [ 47 ] DFT calculations suggest this to be the case for RuO 2 and other rutile oxides.…”
Section: Theoretical Calculationsmentioning
confidence: 64%
“…[69][70][71][82][83][84] For instance, Shao et al observed experimentally and confirmed through modeling that both the mass activity and specific activity decreased when the platinum particle sizes fell below 2.2 nm. For sub-5 nm Pt particles, size makes a profound impact on the ORR activity and stability to influence the oxide binding energies and modify the Pt dissolution path.…”
Section: à2mentioning
confidence: 88%
“…The design of these templates reflects the fact that a number of different kinds of dissolution measurement may be made for inorganic nanoparticles: (1) the (time dependent) concentrations of various species released by dissolution [67,69] (which may be a redox process [69]); (2) the (time dependent) percentage of original nanoparticles dissolved [70]; (3) the (time dependent) dissolution rate [71]. The design of these templates further reflects the fact that dissolution assay protocols typically employ a separation step to isolate the analysed species [61].…”
Section: Physicochemical Characterisation Data Captured By the Templatesmentioning
confidence: 99%